The variability of physical enjoyment, physiological responses, and technical-tactical performance according to the bout duration of small-sided games: a comparative study between female and male soccer players - Farhani, Z.; Amara, S.; Ben Aissa, M.; Guelmami, N.; Bouassida, A.; Dergaa, I. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background This study aimed to compare various factors, namely perceived enjoyment (PE), percentage of peak heart rate (%HRpeak), blood lactate (La), rating of perceived exertion (RPE), and technical-tactical performance among soccer players across different bout durations (CB: continuous bout, MIB: medium intermittent bouts, and SIB: short intermittent bouts) and between male and female players during four-a-side (4vs4) small-sided games (SSGs) including goalkeepers.